SPE Annual Technical Conference and Exhibition 2008
DOI: 10.2118/115028-ms
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing 4D Microgravity To Monitor Water Encroachment

Abstract: The common wisdom is that gravity methods have limited application in the oil industry although they have long been available. The main use of gravity has been for exploration purposes. 4D microgravity monitoring is another new promising gravity application to monitor changes of fluid contacts. Some successful 4D monitoring surveys have been conducted in the industry revealing that this technique is a proven technology in monitoring of gas-water contacts.This paper studies the ability of microgravity to captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…7c blue lines) is slightly different from the initial guess (the straight line x ϭ 10,000 m). At the same time, the residual model gravity fit is 0.2 Gal, which is significantly less than the precision of the existing technology surface measurements, as previously discussed, but higher than the tool precision of~0.01 Gal recommended by Alshakhs et al (2008) as the required tool precision to allow a successful inversion of surface gravity data. Subsequently, for some locations, the resulting OWC is distant from the true OWC by more than 500 m. This illustrates that for this example, the uncertainty of the inversion for the location of the OWC from surface data alone is more than 500 m.…”
Section: Inversion Of Synthetic Datamentioning
confidence: 67%
See 4 more Smart Citations
“…7c blue lines) is slightly different from the initial guess (the straight line x ϭ 10,000 m). At the same time, the residual model gravity fit is 0.2 Gal, which is significantly less than the precision of the existing technology surface measurements, as previously discussed, but higher than the tool precision of~0.01 Gal recommended by Alshakhs et al (2008) as the required tool precision to allow a successful inversion of surface gravity data. Subsequently, for some locations, the resulting OWC is distant from the true OWC by more than 500 m. This illustrates that for this example, the uncertainty of the inversion for the location of the OWC from surface data alone is more than 500 m.…”
Section: Inversion Of Synthetic Datamentioning
confidence: 67%
“…A gravity tool with a very high precision will be required to capture these slight ⌬g changes. Alshakhs et al (2008) generated a synthetic surface microgravity data set by forward modeling using reservoir simulation saturation output. Based on inversion of this synthetic microgravity data, it was concluded that a tool precision of~0.01 Gal is required to be able to successfully detect inter-well fluid substitution changes.…”
Section: The Basic Principles Of Microgravitymentioning
confidence: 99%
See 3 more Smart Citations